PENGARUH BEBAN KERJA DAN KOMPENSASI TERHADAP KINERJA KARYAWAN NITNET CAMAN FOOD GARDEN - Rachmaniar Myrianda Dwiputri; Donny Abdul Latief P; Anggie Meliyani Putri (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2024)
This research aims to determine the effect of workload and compensation on employee performance at Nitnet Caman Food Garden. This research was conducted by distributing questionnaires to Nitnet Caman Food Garden employees. The sample used was a saturated sampling technique, which involved the entire population. The data obtained was tested using regression test analysis. The research results show that workload and compensation have a positive effect on employee performance. The interesting findings of this research show that an increase in workload will increase employee performance. Even though the results of this research show a positive relationship between workload and employee performance, companies still need to consider the suitability of workload so that employee performance can continue to increase, not vice versa. The next finding is that compensation has a positive effect on employee performance, where the compensation provided by the company will improve employee performance.